Effect of edible coating on shelf life of fresh pomegranate arils - Abhishek, Kumar (Journal of Postharvest Technology, 2019)
Pomegranate (Punica granatum L.), grown in tropical and subtropical regions of the world has a long storage life. However, arils when separated from fruits loose quality attributes easily. The present study entitled “Effect of edible coating on fresh pomegranate arils” was conducted at post-harvest technology laboratory of the Department of Horticulture and Post-Harvest Technology, Institute of Agriculture, Palli Siksha Bhavana, Sriniketan, Visva-Bharati University. The experiment was laid out in Completely Randomized Design (CRD), which comprised three replications of six treatments i.e. T1 (0.5 % Chitosan), T2 (0.5 % Chitosan and 1% Ascorbic Acid), T3 (0.75 % Chitosan), T4 (0.75 % Chitosan and 1 % Ascorbic Acid), T5 (1 % Chitosan), T6 (1 % Chitosan and 1 % Ascorbic Acid) and T7 (Control) Chemical Edible coating, arils,parameters viz. total soluble solids (TSS), total sugars, reducing sugar, non-reducing sugars, titratable acidity, anthocyanin content, spoilage loss as well as organoleptic characters of treated arils were evaluated during the investigation. Based on the results obtained from the study, it can be inferred that edible coating of pomegranate arils with 1 % Chitosan proved to be beneficial in maintaining the quality of arils during storage period. Application of 1% Chitosan as edible coating on arils was found promising in maintenance of quality parameters such as total soluble solids, titratable acidity, total sugars, anthocyanin content etc. Therefore, it is concluded that coating of 1 % Chitosan can successfully be used to extend shelf life of pomegranate arils upto 21 days of storage.